장입 슈트 형태에 따른 소결 원료 장입 거동 - 김강민; Kang-min Kim; 이기우; Ki-woo Lee; 권재홍; Jae-hong Kwon; 정해권; Hae-kwon Jeong; 한정환; Jeong-whan Han (대한금속·재료학회지, 55(12), 2017)
In the iron ore sintering process, a thermal imbalance can occur in the sinter feed bed which degrades the quality of the sintered ores. In order to solve this thermal imbalance, it is necessary to control the sizes of the sintering feed charging through the chute by designing an appropriate chute shape, and to improve particle size segregation. In this study, a discrete element method(DEM) simulation was applied to the sinter feed charging process to investigate charging characteristics, such as the escape velocity of particles, size segregation intensity and porosity in the sinter feed bed, depending on the shape of the chute. A charging analysis using three types of chute found that horizontal velocity, segregation intensity and porosity in the lowest position in the bed were the highest when a curved chute was used. Therefore, it seems that a curved chute would be effective for solving the thermal imbalance caused by segregation charging. However, in order to use a curved chute, it is necessary to find a way to maintain uniform permeability in the sinter feed bed. (Received May 23, 2017; Accepted August 30, 2017)